2022
DOI: 10.1590/0047-2085000000373
|View full text |Cite
|
Sign up to set email alerts
|

A vitamina C na esquizofrenia apresenta benefício? Estudo preliminar com análise comportamental em ratos

Abstract: RESUMO Objetivo O objetivo deste estudo foi analisar em ratos modelos de esquizofrenia, induzidos pela administração de cetamina, a possibilidade dos efeitos benéficos do ácido ascórbico na esquizofrenia, por meio do teste comportamental. Métodos O estudo preliminar foi simples-cego e randomizado. Foi realizado o protocolo de psicose por cetamina em 24 ratos Wistar submetidos posteriormente à análise comportamental. No primeiro grupo, foram administradas: água e cetamina; no segundo: ácido ascórbico e ceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In the scientific research field, initiatives that seek to assess other agents may soon help to alleviate the dilemma of loss reduction versus long-term effects of antipsychotics. Thence, the relevance of the Okamoto et al 5 study is identified in this number. The researchers conducted a study in rat models of schizophrenia to analyse the possibility of beneficial effects of ascorbic acid in schizophrenia.…”
mentioning
confidence: 99%
“…In the scientific research field, initiatives that seek to assess other agents may soon help to alleviate the dilemma of loss reduction versus long-term effects of antipsychotics. Thence, the relevance of the Okamoto et al 5 study is identified in this number. The researchers conducted a study in rat models of schizophrenia to analyse the possibility of beneficial effects of ascorbic acid in schizophrenia.…”
mentioning
confidence: 99%